Human cultured cells are capable to incorporate isolated plant mitochondria loaded with exogenous DNA - Klimenko, E.S.; Zaporozhchenko, I.A.; Mileyko, V.A.; Morozkin, E.S.; Koulintchenko, M.V.; Laktionov, P.P.; Konstantinov, Yu.M. (Вiopolymers and Cell, 2012)
Aim. To investigate the possibility of human cultured cells to incorporate isolated mitochondria together with exogenous DNA introduced into organelles. Methods. Two approaches were used for this purpose, fluorescent labelling of mitochondria and/or DNA with subsequent analysis of the cells subjected to incubation by microscopy or by quantitative PCR. Results. We have shown that human cultured cells lines, HeLa and HUVEC, are capable to uptake isolated plant mitochondria and that this process depends on the incubation time and concentration of organelles present in medium. The incorporated mitochondria can serve as vehicles to deliver exogenous DNA into human cells, this DNA is then distributed in different cell compartments. Conclusions. These results are preliminary and need further investigations, including testing the possibility of human cells to incorporate the mitochondria of human or animal origin and creating genetic construction which could provide certain selectivity or stability of the transferred exogenous DNA upon cell uptake of the mitochondria as vectors.
Keywords: human cultured cells, DNA-loaded mitochondria, xenotransplantation. Мета. Вивчення можливості поглинання клітинами ліній HeLa і HUVEC ізольованих клітинних мітохондрій, попередньо навантажених чужорідною ДНК. Методи. Використано два методичних підходи: флуоресцентне мічення мітохондрій і/або мтДНК та кількісний ПЛР-аналіз ДНК інкубованих з мітохондріями клітин. Результати. Продемонстровано, що клітини людини ліній HeLa і HUVEC здатні поглинати ізольовані рослинні мітохондрії, і цей процес залежить від часу інкубації і концентрації органел у середовищі. Мітохондрії, таким чином, можуть слугувати векторною системою для доставки чужорідної ДНК у клітини людини. ДНК, яка транспортується мітохондріями, розподіляється у різних клітинних компартментах. Висновки. Отримані результати мають попередній характер і дозволяють почати перевірку можливості поглинання клітинами людини мітохондрій тваринного походження (у тому числі мітохондрій людини) та створення генетичних конструкцій, які містять селективний ген і забезпечують стабільне підтримання транспортованої мітохондріями екзогенної ДНК після поглинання їх клітинами.
Ключові слова: клітини людини в культурі, навантажені ДНК мітохондрії, ксенотрансплантація. Цель. Изучение возможности поглощения клетками линий HeLa и HUVEC изолированных растительных митохондрий, предварительно нагруженных чужеродной ДНК. Методы. Использованы два методических подхода: флуоресцентное мечение митохондрий и/или мтДНК и количественный ПЦР-анализ ДНК инкубированных с митохондриями клеток. Результаты. Продемонстрировано, что клетки человека линий HeLa и HUVEC способны поглощать изолированные растительные митохондрии, и этот процесс зависит от времени инкубации и концентрации органелл в среде. Митохондрии, таким образом, могут служить векторной системой для доставки чужеродной ДНК в клетки человека. Транспортируемая митохондриями ДНК распределяется в различных клеточных компартментах. Выводы. Полученные результаты имеют предварительный характер и позволяют приступить к проверке возможности поглощения клетками человека митохондрий животного происхождения (в том числе митохондрий человека) и созданию генетических конструкций, включающих селективный ген и обеспечивающих стабильное поддержание транспортируемой митохондриями экзогенной ДНК после их поглощения клетками.
Ключевые слова: клетки человека в культуре, нагруженные ДНК митохондрии, ксенотрансплантация.